Study thermal characteristics of millet grain, dried in the machine with the swirling flow of the coolant and the microwave energy supply - S. T. Antipov (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2016)
The article discusses the problems of determining the thermal characteristics of millet. The choice of the research object. The paper presents the principle of operation of the plant and the parameters of the standard, organic glass for measurements. Method was to study millet grains and organic glass, which are brought into contact on a common plane. The heater is brought into contact with the product and passed the constant heat flow, which passed through a layer of millet grain at different speeds. As a result, the temperature in the contact plane of the changed and recorded on the chart of the potentiometer in the form of the curve, by which you can determine the time and temperature change. The thermal diffusivity and thermal conductivity determined by empirical formulas obtained by solving a system of differential equations, made up for the system of two bodies, one of which includes the unknown thermal characteristics. Test two bodies in contact on a common plane, resulting in mathematical physics principles constitute two differential equations with uniform initial and boundary conditions of the first kind, due to the parameters of ongoing experience. It is a plot of thermal performance of the temperature and humidity. Revealed linear dependence of the physical thermal characteristics, showing that with increasing temperature the thermal diffusivity value decreases, and the thermal conductivity and specific heat capacity are increasing character. Revealed the equations describing the thermal characteristics of millet grain with a humidity in the range of 13.6–35.1% and the temperature range 293–373 K.